2019
DOI: 10.1002/pds.4747
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of date of death recording in the Clinical Practice Research Datalink GOLD database in England compared with the Office for National Statistics death registrations

Abstract: Purpose It is not clear whether all deaths are recorded in the Clinical Practice Research Datalink (CPRD) or how accurate a recorded date of death is. Individual‐level linkage with national data from the Office for National Statistics (ONS) and Hospital Episode Statistics (HES) in England offers the opportunity to compare death information across different data sources. Methods Age‐standardised mortality rates (ASMRs) standardised to the European Standard Population (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…CPRD with linkage to HES–ONS death registry data has been shown previously to be sufficient for censoring follow‐up and calculating mortality. 48 We demonstrate that patients with diabetic gastroparesis had an almost twofold mortality to those with idiopathic gastroparesis, after adjusting for significant predictors.…”
Section: Discussionmentioning
confidence: 72%
“…CPRD with linkage to HES–ONS death registry data has been shown previously to be sufficient for censoring follow‐up and calculating mortality. 48 We demonstrate that patients with diabetic gastroparesis had an almost twofold mortality to those with idiopathic gastroparesis, after adjusting for significant predictors.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies using CPRD data have shown to be highly valid, with for example for hip fractures over 90% confirmed diagnoses [14]. CPRD GOLD had a high quality of recording of all-cause mortality [15].…”
Section: Source Populationmentioning
confidence: 95%
“…For example, many studies removed patients with missing data among any variable from the study entirely, did not adequately define their predictor variables, or did not assess correlation between predictors. Additionally, only two studies using data from electronic medical records assessed the quality of the data before building the model, which is often considered an important step in these datasets because they were not designed for use in research studies and often require some form of data validation before analysis [71][72][73][74].…”
Section: Fbc-based Prediction Modelsmentioning
confidence: 99%